Diversidade taxonômica, funcional e filogenética de protistas ciliados em uma planície de inundação Neotropical: determinantes dos padrões espaciais e temporais da diversidade β e sincronia de comunidade. - Oliveira, Felipe Rafael de (2022)
Patterns of species richness are driven by biotic and abiotic factors and the way in which they operate at spatial and temporal scales. In continental aquatic environments, communities may differ in important aspects such as taxonomic, functional and phylogenetic structure, and the detection of biodiversity may vary between these different facets. For the development of this study, to test important ecological theories, we used the spatial and temporal database of ciliate protists from the upper Paraná River floodplain, from a long-term ecological program - PELD. The spatial and temporal β diversity was verified in three facets of biodiversity (taxonomic, functional and phylogenetic) of the ciliate community, and the contribution of different environmental predictors, using data on composition (presence/absence) and structure (abundance) of the community. It was found that different facets of diversity are influenced by different environmental predictors, but with more evident results for the functional and phylogenetic facets, especially when using data on the structure of the ciliate community. The synchrony between ciliate species in time and space was also evaluated, and the relation of this synchrony with the facets of diversity. Significant relationships were observed between ciliate synchrony and phylogenetic distance, but not for community functional distance. It is concluded that systematic and more precise advances in the community are needed to further improve knowledge about phylogenetic proximities of species and ecosystem functions performed by ciliate protists in limnic environments. Therefore, studies with functional and phylogenetic characteristics of ciliate species are recommended, in future research with application in other ecological theories, with significant contributions in the field of ecology, taxonomy and conservation of this community.